USE OF NON-TRADITIONAL METHODS IN TEACHING SPECIALIZED SUBJECTS - Salikhova Mukhayyo Shakirovna (Western European Studies, 2025)
This article studies the importance and effectiveness of non-traditional teaching methods in teaching specialized subjects. Unlike traditional teaching methods, interactive, innovative and independent approaches play an important role in deepening students' knowledge, increasing their interest and forming practical skills. Non-traditional methods include project-based learning and collaborative group work. The article analyzes the advantages of these methods and methods of their implementation in the teaching process
Keywords: Specialized Disciplines; Non-Traditional Methods; Quality Of Education